(untitled) (The Science Post, 2025)
The increasing complexity of healthcare systems demands innovative approaches to improve patient outcomes while reducing costs and resource inefficiencies. Data-driven predictive modeling has emerged as a transformative tool for healthcare decision-making, enabling clinicians and policymakers to forecast disease progression, optimize treatment plans, and allocate resources more effectively. By leveraging diverse datasets—ranging from electronic health records (EHRs) to medical imaging and real-time patient monitoring—predictive models can provide early warnings of health risks and support evidence-based clinical decisions. This paper explores the role of predictive analytics in healthcare, emphasizing its applications in disease prediction, patient stratification, and personalized medicine. Furthermore, it highlights the challenges of data quality, ethical considerations, and the integration of machine learning models into clinical workflows. A systematic review of current approaches demonstrates the growing importance of predictive modeling for advancing patient-centered care. The findings suggest that predictive modeling not only enhances healthcare outcomes but also promotes efficiency, safety, and sustainability across healthcare systems.